2016
DOI: 10.1002/2016gl070418
|View full text |Cite
|
Sign up to set email alerts
|

Geological structures control on earthquake ruptures: The Mw7.7, 2013, Balochistan earthquake, Pakistan

Abstract: The 2013 Mw7.7 Balochistan earthquake, Pakistan, ruptured the Hoshab fault. Left‐lateral motion dominated the deformation pattern, although significant vertical motion is found along the southern part of the rupture. Correlation of high‐resolution (2.5 m) optical satellite images provided horizontal displacement along the entire rupture. In parallel, we mapped the ground rupture geometry at 1:500 scale. We show that the azimuth of the ground rupture distributes mainly between two directions, N216° and N259°. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…In summary, building upon earlier observations by Fletcher et al () and Teran et al (), we demonstrate the importance of inherited structures in guiding the surface rupture trace of the El Mayor‐Cucapah earthquake and controlling variations in shallow slip magnitude along it. This work adds to a growing number of studies that highlight the first‐order role of geological fabric in governing the surface expression of large earthquakes, as well as the importance of high‐resolution imagery and imaging geodesy in resolving this behavior (e.g., Avouac et al, ; Choi et al, ; Lee et al, ; Vallage et al, ; Yue et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…In summary, building upon earlier observations by Fletcher et al () and Teran et al (), we demonstrate the importance of inherited structures in guiding the surface rupture trace of the El Mayor‐Cucapah earthquake and controlling variations in shallow slip magnitude along it. This work adds to a growing number of studies that highlight the first‐order role of geological fabric in governing the surface expression of large earthquakes, as well as the importance of high‐resolution imagery and imaging geodesy in resolving this behavior (e.g., Avouac et al, ; Choi et al, ; Lee et al, ; Vallage et al, ; Yue et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Although the earthquake risk for these faults is considered lower due to lack of Holocene activity, the faults may still be important for models of hazard or fault zone evolution. Furthermore, recent work has demonstrated that earthquakes may propagate across both active and inactive structures in the same event (Vallage et al, 2016). The strike of the potentially active fault along the waterfront suggests that it may be a northern continuation of the offshore Coronado fault zone, which is included in AP zone regulations (Fig.…”
Section: Hazard Classificationmentioning
confidence: 99%
“…It could also be interpreted that all faults are part of the same active zone with the less potentially active faults and potentially active faults representing evolutionary phases of the system that shut off as the main faults were established. Other recent examinations of fault zone geometry used high-resolution surface mapping technology (e.g., lidar) across greater fault zone extents, and included more information on fault dip, sense of slip, and fault zone width (e.g., Barth et al, 2012;Teran et al, 2015;Vallage et al, 2016;Scott et al, 2018). These studies were also conducted in undeveloped areas, which again highlights the relative difficulty of assessing fault zones through urban areas where much of this information is not available.…”
Section: Fault Zone Geometrymentioning
confidence: 99%
“…High‐resolution rupture maps, involving an unprecedented level of detail for rupture geometries and lateral slip variations, have started to become available in the last decade due to progressive availability for civil researchers of submetric optical satellite images (e.g., Klinger et al, ; Xu et al, ). In parallel, new remote sensing methodologies have improved our capacity to measure horizontal and vertical displacements down to the actual rupture trace with a resolution of only few meters (Grandin et al, ; Klinger et al, ; Vallage et al, , ). Eventually, these new data sets are starting to be introduced in numerical rupture models, although the current level of data complexity is still beyond standard modeling capacities (e.g., Duan & Oglesby, ; Finzi & Langer, ; Harris & Day, ; Hu et al, ; Lozos et al, ; Oglesby et al, ; Thomas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, these new data sets are starting to be introduced in numerical rupture models, although the current level of data complexity is still beyond standard modeling capacities (e.g., Duan & Oglesby, ; Finzi & Langer, ; Harris & Day, ; Hu et al, ; Lozos et al, ; Oglesby et al, ; Thomas et al, ). Earthquakes that were recently documented demonstrate that inherited fault geometries, such as fault bends, steps, branches, and their related segment geometry, can control the propagation and path of an earthquake rupture (Choi et al, ; Haeussler et al, ; Klinger et al, ; Lettis et al, ; Vallage et al, ; Wesnousky, ) and the rupture history over multiple seismic events (Klinger et al, , ; Schwartz et al, ; Zielke et al, ). These results have been regarded as key parameters to assess potential for rupture of large earthquakes in given active fault systems, with significant implications for seismic hazard (Mignan et al, ).…”
Section: Introductionmentioning
confidence: 99%